Improving hemodynamics of cardiovascular system under a novel intraventricular assist device support via modeling and simulations. (31st October 2017) - Zhu, Shidong; Luo, Lin; Yang, Bibo; Li, Xinghui; Wang, Xiaohao
Abstract: Ventricular assist devices (LVADs) are increasingly recognized for supporting blood circulation in heart failure patients who are non-transplant eligible. Because of its volume, the traditional pulsatile device is not easy to implant intracorporeally. Continuous flow LVADs (CF-LVADs) reduce arterial pulsatility and only offer continuous flow, which is different from physiological flow, and may cause long-term complications in the cardiovascular system. The aim of this study was to design a new pulsatile assist device that overcomes this disadvantage, and to test this device in the cardiovascular system. Firstly, the input and output characteristics of the new device were tested in a simple cardiovascular mock system. A detailed mathematical model was established by fitting the experimental data. Secondly, the model was tested in four pathological cases, and was simulated and coupled with a fifth-order cardiovascular system and a new device model using Matlab software. Using assistance of the new device, we demonstrated that the left ventricle pressure, aortic pressure, and aortic flow of heart failure patients improved to the levels of a healthy individual. Especially, in state IV level heart failure patients, the systolic blood pressure increased from 81.34 mmHg to 132.1 mmHg, whereas the diastolic blood pressure increased from 54.28 mmHg to 78.7 mmHg. Cardiac output increased from 3.21 L/min to 5.16 L/min. The newly-developed assist device not only provided a physiological flow that was similar to healthy individuals, but also effectively improved the ability of the pathological ventricular volume. Finally, the effects of the new device on other hemodynamic parameters are discussed.